2022
DOI: 10.1182/bloodadvances.2021006293
|View full text |Cite
|
Sign up to set email alerts
|

Preferential expansion of CD8+ CD19-CAR T cells postinfusion and the role of disease burden on outcome in pediatric B-ALL

Abstract: T cells expressing CD19-specific chimeric antigen receptors (CD19-CARs) have potent antileukemia activity in pediatric and adult patients with relapsed/refractory B-cell acute lymphoblastic leukemia (B-ALL). However, not all patients achieve a complete response (CR), and a significant percentage relapse after CD19-CAR T-cell therapy due to T-cell intrinsic and/or extrinsic mechanisms. Thus, there is a need to evaluate new CD19-CAR T-cell products in patients to improve efficacy. We developed a Phase 1/2 clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 51 publications
5
20
0
Order By: Relevance
“…To determine features of effective CAR T cell therapies, we undertook a comprehensive gene expression profiling of 16 pediatric patients with relapsed/refractory B-ALL, 15 of whom had received autologous T cells expressing a CD19.4-1BBz CAR (CD19-CAR) (9,10) post lymphodepleting chemotherapy on our investigator-initiated clinical study (NCT03573700; Fig 1A). Patients 0 through 12 have been reported in detail elsewhere (11). Twelve out of the 15 patients who were infused with CAR T cells achieved a complete response (CR), with 11/12 CRs being measurable residual disease negative (MRDneg) at four weeks post CD19-CAR T cell infusion (see Supplementary Clinical Information).…”
Section: Pre-and Post-infusion Car T Cells Have Distinct Gene Express...mentioning
confidence: 99%
See 3 more Smart Citations
“…To determine features of effective CAR T cell therapies, we undertook a comprehensive gene expression profiling of 16 pediatric patients with relapsed/refractory B-ALL, 15 of whom had received autologous T cells expressing a CD19.4-1BBz CAR (CD19-CAR) (9,10) post lymphodepleting chemotherapy on our investigator-initiated clinical study (NCT03573700; Fig 1A). Patients 0 through 12 have been reported in detail elsewhere (11). Twelve out of the 15 patients who were infused with CAR T cells achieved a complete response (CR), with 11/12 CRs being measurable residual disease negative (MRDneg) at four weeks post CD19-CAR T cell infusion (see Supplementary Clinical Information).…”
Section: Pre-and Post-infusion Car T Cells Have Distinct Gene Express...mentioning
confidence: 99%
“…The clinical grade lentiviral vector encoding the CD19.4-1BBz CAR, and CD19-CAR T cell products were manufactured at the Children's Good Manufacturing Practice facility of St. Jude. The study, lentiviral vector, and the manufacturing of autologous CD19-CAR T cells is described in detail elsewhere (11).…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using single-cell sequencing, we identify a rare population of HHV-6 ‘super-expressors’ (~1 in 300-10,000 cells) that possess high viral transcriptional activity in chimeric antigen receptor (CAR) T cell culture before spreading to infect other cells in vitro . Through the analysis of single-cell sequencing data from patients receiving cell therapy products that are FDA-approved 2 or used in clinical studies 3,4 , we identify the presence of CAR+, HHV-6 super-expressor T cells in vivo . Together, our study implicates cell therapy products as a source of lytic HHV-6 reported in clinical trials 1,57 and has broad implications for the design, production, and monitoring of cell therapies.…”
mentioning
confidence: 99%